Anthrax retrospective analysis in endemic areas using enzyme-linked immunosorbent assay (ELISA) - Hardjoutomo, S; Poerwadikarta, M.B (Indonesian Journal of Animal and Veterinary Sciences, 1996)
About the end of 1995, an infectious disease among buffaloes as well as human beings was reported to occur in the District of Ngada, East Nusatenggara . Specimens of death animals, namely a piece of bones, hide, soil samples as well as blood and exudate smears and sera of the local inhabitants were submitted to Balitvet, Bogor laboratory for diagnosis . Bacteriological examinations of those specimens revealed that B. Anthracis was the causative agent of the disease . Along the line, 40 humans sera comprised 20 sera of local exposed inhabitants and 20 sera of non-exposed outsider, examined by the antibody enzyme-linked immunosorbent assay (ELISA) confirmed the diagnosis . It was concluded that antibody ELISA is one of diagnosis tools for analyzing of an anthrax outbreak in the field . Â  Keywords : Anthrax, retrospective analysis, antibody ELISA; serum